Nanohybrids of Pt-Functionalized Al2O3/ZnO Core-Shell Nanorods for High-Performance MEMS-Based Acetylene Gas Sensor - Kondalkar, Vijay V.; Duy, Le Thai; Seo, Hyungtak; Lee, Keekeun (ACS Applied Materials and Interfaces, 2019)
Metal oxide nanostructures are the most promising materials for the fabrication of advanced gas sensors. However, the main challenge of these gas sensors is humidity interference and issues related to the selectivity and high operating temperature, which limits their response in real-time applications. In this study, we proposed nanohybrids of Pt-functionalized Al2O3/ZnOcore-shell nanorods (NRs) for a real-time humidity-independent acetylene gas sensor. The core ZnO NRs have been fabricated on microelectromechanical system (MEMS) microheater, followed by a coating of a thin nanoscale moisture-blocking conformal Al2O3 shell by atomic layer deposition (ALD) and decoration of Pt NPs using photochemical deposition and e-beam evaporation. Prior to the fabrication, a COMSOL simulation was performed to optimize the microheater design and moisture-blocking layer thickness. A comparative study of the decoration of Pt NPs on the ZnO surface by photochemical (s-Pt/ZnO) and e-beam evaporation (e-Pt/ZnO) and a Al2O3 thin moisture-blocking shell layer (Pt/Al2O3/ZnO) in sensor response has been conducted. The fabricated sensors (s-Pt/ZnO) and (e-Pt/ZnO) showed a high response Î"R/R (%) of 96.46% and 68.15% to 200 ppm acetylene at 120 °C and detect trace concentrations of acetylene down to 1 ppm, but the response is influenced by humidity. Moreover, the sensor (Pt/Al2O3/ZnO) exhibited nearly the same sensing characteristics and high acetylene selectivity despite the wide range of humidity variation from 20% RH to 70% RH. The Pt-functionalized Al2O3/ZnOcore-shell NR-based sensor showed better sensing and stable performance than other sensors (s-Pt/ZnO and e-Pt/ZnO) under humidity conditions.
Keywords: Acetylene gas; High operating temperature; Humidity interference; Micro electromechanical system (MEMS); Microheater; Photochemical deposition; Pt nanoparticles; Sensing characteristics; acetylene gas sensor; Al2O3/ZnO; humidity interference; microheater; Pt nanoparticles; selectivity